EVIDANCE BASED CASED REPORT (EBCR) : PENGARUH PEMERAHAN TALI PUSAT TERHADAP KADAR HEMOGLOBIN PADA BAYI BARU LAHIR (Jurnal Kesehatan Siliwangi, 2022)
Background: Clamping and cutting the umbilical cord is part of the activity of Normal Childbirth Care (APN) which is included in the active management of the third stage. Cutting the umbilical cord can minimize the increase in blood volume so that placental transfusion will experience a loss of 33% iron. Iron deficiency can take babies at risk of being infected with anemia until the age of 4 months. Milking the umbilical cord is an alternative way that has the purpose to provide the optimal placental transfusion in infants to reduce the risk of anemia on baby growth. Purpose: This evidence-based case report aims to determine the effect of umbilical cord milking on hemoglobin levels in newborns. Method: The researcher has been found the articles about the effect of milking the umbilical cord on hemoglobin levels in newborns and it was conducted through the PubMed and Cochrane databases. There are 2 articles by Kilicdag, Jeevan, and the team that matched the inclusion and exclusion criteria which were then critically analyzed. Result: The results of measuring hemoglobin levels in infants who received intervention when they were 38 hours old were 23.8 gr/dL. This shows that infants who received cord milking interventions had higher hemoglobin levels compared to infants without cord milking. Conclusion: From these two articles, it can be concluded that umbilical cord milking is proven to be the right strategy for increasing hemoglobin levels in newborns.